Conceptual design of advanced fusion neutron source (A-FNS) and irradiation test modules. (16th September 2021) - Sato, S.; Kasugai, A.; Ochiai, K.; Masuda, K.; Nakamura, M.M.; Ohta, M.; Oyaidzu, M.; Kwon, S.; Sakamoto, K.; Ishida, S.
Abstract: We have established a conceptual design of Advanced Fusion Neutron Source (A-FNS). In order to obtain irradiation data required in qualifying materials of fusion DEMO DT reactor, we newly designed nine test modules (TMs) to be implemented in the A-FNS. The design of the test modules is based on a new distinctive maintenance scheme: 'horizontal maintenance method integrated with the shielding plug'. By integrating the TMs with the shield plug and transferring those from the test cell to the access cell, we can avoid disconnecting and connecting the huge amounts of the pipes and cables by means of the remote handling inside the test cell. We determined a configuration of the TMs in the test cell so as to achieve the required irradiation data for each of the test modules. The maximum dpa of F82H specimens in the TM for blanket structural material was about 10 dpa/fpy, which was designed to fulfil critical requirement by accumulated irradiation for two years and operation duration for four years with the operation availability of 50%. A-FNS was designed so that the huge amounts of neutrons generated can be utilized for various non-fusion purposes as well as the fusion materials irradiation. We newly designed a module to produce the significant amount of 99 Mo for a medical purpose. The module for such a non-fusion purpose can be installed in the test cell with the compatibility of the fusion materials irradiation tests.